Immunization status and immune response to HBV vaccine among HCWs: a report from tertiary care centre in India - Haridas, Hitha; Das, Priyanka; Tamilarasan, Gopi; Marwal, Robin; Rakshit, Partha; Kabra, Sandya; Gaind, Rajni (International Journal Of Community Medicine And Public Health, 2025)
Background: Healthcare workers (HCWs) are at a high risk of acquiring hepatitis B virus (HBV) infection which is preventable through hepatitis B vaccination. Hepatitis B surface antibody (anti-HBs) titre (≥10 mIU/ml) is a marker for protective immune response. The aim of this study was to evaluate HBV vaccination status and study factors affecting anti- HBs titres among the HCWs. Methods: This cross-sectional study was conducted over 18 months and 1000 HCWs were enrolled. Personal, demographic and detailed HBV vaccination history were collected using predesigned proforma. Anti‑HBs titre, were assessed by ELISA irrespective of the vaccination status. The HCWs with non-protective titres were screened for prior infection (HBsAg and Anti- HBc). All data were analysed using SPSS v21. Results: Majority of HCWs (606) were completely vaccinated, 279 partially vaccinated and 115 unvaccinated. Vaccination compliance was significantly higher among the doctors and female HCWs. Among fully vaccinated HCWs non protective titres were recorded in 6.3%. Incomplete vaccination, male gender, smoking, and alcohol consumption were predictors of nonprotective titres. There was a significant fall in anti-HBs titres with time (p value =0.04). None of the HCWs had acute or previous HBV infection. Conclusions: Study highlights the poor compliance to HBV vaccination among HCWs. In health care setting vaccination must be made mandatory for all HCWs at induction and documented by vaccination card. As anti-HBs titter decline with time, evaluation must be performed 1-2 months after the third dose and documented for guiding therapy following occupational exposure.